Analysis of the Determining Factors Influencing Accounting Students’ Interest in Pursuing Careers in Islamic Financial Institutions - Mytha Chandra Dewi; Indira Januarti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of religiosity, personality, knowledge of Islamic accounting, and job market considerations on accounting students’ interest in pursuing careers in Islamic financial institutions. The research adopts the Theory of Planned Behavior, which is an extension of the Theory of Reasoned Action. The study population comprises undergraduate accounting students from universities in Indonesia who have taken Islamic accounting courses. This research employs a quantitative approach. The data used are primary data collected through an online questionnaire survey. The sampling technique used is convenience sampling, which involves selecting samples based on ease of access or respondent availability. Variable measurement is carried out through statements presented to students using a Likert scale ranging from 1 to 5. The sample size was determined using the Lemeshow formula, and this study obtained 155 respondents from several universities in Indonesia, including Universitas Islam Indonesia, Universitas Muhammadiyah Yogyakarta, Universitas Islam Negeri Sunan Kalijaga, Universitas Islam Negeri Walisongo, Universitas Islam Sultan Agung, and Universitas Muhammadiyah Semarang. The analysis tool used was IBM SPSS version 26 software. Data analysis was conducted using multiple linear regression. The results showed that personality and knowledge of Islamic accounting have a positive influence on accounting students' interest in pursuing careers in Islamic financial institutions. Conversely, religiosity and job market considerations do not have a positive effect on accounting students’ career interest in Islamic financial institutions.